2015
DOI: 10.1007/s10495-015-1198-x
|View full text |Cite
|
Sign up to set email alerts
|

Anti-tumor activities of luteolin and silibinin in glioblastoma cells: overexpression of miR-7-1-3p augmented luteolin and silibinin to inhibit autophagy and induce apoptosis in glioblastoma in vivo

Abstract: Glioblastoma is the deadliest brain tumor in humans. High systemic toxicity of conventional chemotherapies prompted the search for natural compounds for controlling glioblastoma. The natural flavonoids luteolin (LUT) and silibinin (SIL) have anti-tumor activities. LUT inhibits autophagy, cell proliferation, metastasis, and angiogenesis and induces apoptosis; while SIL activates caspase-8 cascades to induce apoptosis. However, synergistic anti-tumor effects of LUT and SIL in glioblastoma remain unknown. Overexp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
66
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(71 citation statements)
references
References 36 publications
2
66
1
Order By: Relevance
“…It was found that 20 µM and 50 µM concentrations almost completely blocked tumor cell invasion, inhibiting cell proliferation and migration of glioblastoma cells. On the other hand, silymarin stimulates the process of apoptosis by activating caspases [40]. It is also a confirmation of the results of our own study, where it was observed that self-acting silymarin induces the death of glioblastoma cells.…”
Section: Discussionsupporting
confidence: 90%
“…It was found that 20 µM and 50 µM concentrations almost completely blocked tumor cell invasion, inhibiting cell proliferation and migration of glioblastoma cells. On the other hand, silymarin stimulates the process of apoptosis by activating caspases [40]. It is also a confirmation of the results of our own study, where it was observed that self-acting silymarin induces the death of glioblastoma cells.…”
Section: Discussionsupporting
confidence: 90%
“…21 miRNAs are reported to be involved in luteolin's anticancer activity. 18,22 Chakrabarti and Ray discovered that luteolin induced apoptosis in glioblastoma by regulating miR-7-1-3p expression. 18 Yang et al found that miR-6809-5p mediated luteolin-induced anticancer effects by targeting flotillin 1 in hepatoma.…”
mentioning
confidence: 99%
“…The effect was mediated through induction of apoptosis and full blockade of invasion and migration, through suppression of protein kinase C, downregulation of iNOS and induction of miR-7-1-3p. The flavonoid combination also inhibited rapamycin-induced autophagy, a pathway that can cause survival of cells [5]. A study by Chang et al showed that angiotensin II is able to induce apoptosis in endothelial cells, which could be suppressed by atorvastatin, the lipid-lowering drug Lipitor [6].…”
Section: The Editors’ Choicementioning
confidence: 99%